Msx genes delineate a novel molecular map of the developing cerebellar neuroepithelium - Gupta, Ishita; Yeung, Joanna; Rahimi-Balaei, Maryam; Wu, Sih-Rong; Goldowitz, Dan (Frontiers in Molecular Neuroscience, 2024)
In the early cerebellar primordium, there are two progenitor zones, the ventricular zone (VZ) residing atop the IVth ventricle and the rhombic lip (RL) at the lateral edges of the developing cerebellum. These zones give rise to the several cell types that form the GABAergic and glutamatergic populations of the adult cerebellum, respectively. Recently, an understanding of the molecular compartmentation of these zones has emerged. To add to this knowledge base, we report on the Msx genes, a family of three transcription factors, that are expressed downstream of Bone Morphogenetic Protein (BMP) signaling in these zones. Using fluorescent RNA in situ hybridization, we have characterized the Msx (Msh Homeobox) genes and demonstrated that their spatiotemporal pattern segregates specific regions within the progenitor zones. Msx1 and Msx2 are compartmentalized within the rhombic lip (RL), while Msx3 is localized within the ventricular zone (VZ). The relationship of the Msx genes with an early marker of the glutamatergic lineage, Atoh1, was examined in Atoh1-null mice and it was found that the expression of Msx genes persisted. Importantly, the spatial expression of Msx1 and Msx3 altered in response to the elimination of Atoh1. These results point to the Msx genes as novel early markers of cerebellar progenitor zones and more importantly to an updated view of the molecular parcellation of the RL with respect to the canonical marker of the RL, Atoh1.